Characterization of Semi-Interpenetrated Network Alginate/Gelatin Wound Dressing Crosslinked at Sol Phase - Dian Pribadi Perkasa; Erizal Erizal; Tri Purwanti; Alva Edy Tontowi (Indonesian Journal of Chemistry, 2018)
Gel contraction of alginate during ionic crosslinking at sol phase was reduced by blending with gelatin solution due to intermolecular interaction and chain entanglement. The semi-interpenetrated network (semi-IPN) of wound dressing hydrogels were prepared by overlaid alginate/gelatin blend with 1.0% (w/w) CaCl2 solution under ambient temperature for 2 h. Results showed that gel contraction was significantly reduced with increasing gelatin content i.e. from 40.5 ± 5.8% for pure alginate to as low as 5.8 ± 1.2% for alginate/gelatin of 1:7 (w/w). It seems that gelatin successfully inhibited alginate chains mobility during their network re-arrangement by Ca2+ cation. The FTIR spectra of hydrogels showed combination of characteristic vibration of alginate and gelatin. Increasing gelatin content also significantly improved elasticity and tensile strength at break of dried hydrogels. Swelling kinetics of dried hydrogels were fitted Schott’s second-order power-law model. Increasing gelatin fraction increased the swelling rate while decreased the swelling at equilibrium. Their absorptive capacity were of interval for management of moderate to heavily exudating wound.